The Effects of Surprising Events on Promoting Social Change in Unwinnable Persuasive Games - Reza Giga Isnanda; Paulus Insap Santosa; Rudy Hartanto (Serious Games Society, 2023)
Surprising events can be beneficial for unwinnable persuasive games, especially since they can evoke players to reflect on their failure to win the game. Despite its presence in some titles, the usage of surprising events still lacks empirical support. This study aims to gain insight into it by comparing the effects of revealing the game's context from the beginning to delaying it until the game ends. In addition, we also examine the interaction effects with playing duration since it is possible that longer playtime will lead to smaller effects for a game with surprising events, whereas longer playtime will result in greater effects for a game without surprising events. To do so, we conducted a 2 x 2 factorial between-subject experiment with an additional no-treatment control group. The results suggest that delaying the revelation to create a surprising event can promote the same level of donation from players, regardless of their playing time. On the other hand, longer playtime is important if players know the context from the beginning. Additional results about the effect of playing duration on donation and willingness to help were also discussed in this paper.